Studies on the Performance of Poultry Farming Enterprises in Nadia District of West Bengal - Roy, Arnab (International Journal of Livestock Research, 2019)
The study focused on the economics of poultry farms in Nadia district of West Bengal state. Both primary and secondary data were used. The present study has been conducted based on primary and secondary data. The primary data was collected from 120 poultry farms and 20 market intermediaries selected randomly using pre-tested questionnaires. The broiler as well as the layer farming in poultry enterprise has been found profitable in Nadia district of West Bengal. However, there is still enough scope in reducing the cost of production and increasing the profitability in poultry farming. The study is based on primary and secondary data collected from 120 poultry farmers by adopting purposive sampling. The total fixed cost in layer farming was estimated to be 0.66 per cent of the total cost for 1000 birds per batch. The return structure of layer farms indicates the total returns from the sale of eggs, sale of culled birds and manure from 1000 birds as Rs. 424590. Among the overall total returns, the sale of eggs accounted for about 86.39 per cent followed by sale of culled birds (9.1 per cent). As regards marketing of egg, there was only two channels of marketing. Thus, producers' share in consumer's rupee was observed 79.23% and 56.50 % respectively. Garrett’s ranking technique was used to identify the constraints in the poultry farming and marketing in the study area. The study recommends feed subsidies by the government, provision of adequate incentives and supporting services to broiler producers as well as organizing training workshops to increase profitability of broiler production.